Effect of using bone cement (Methyl methacrylate) and lumbar drain in the managing of refractory Cerebrospinal fluid (CSF) leak in the anterior skull base defect, case report - Amjad Alduhaish; Faisal Farrash; Ilyas Othman; Gassan Alokby; Sulaiman Hosaini; Peter Spangenberg (Interdisciplinary Neurosurgery, 2021)
Background: Cerebrospinal Fluid (CSF) leaks usually happen after damaging the cribriform plate due to trauma, and it’s less likely spontaneous. Case Description: We are presenting a case that suffered from spontaneous refractory CSF leak which did not resolve after multiple surgical interventions. During treatment, a decision was made to place a lumbar drain to promote healing and recovery. Once the drain was removed, the patient deteriorated suddenly. Decompressive craniectomy was performed with transcranial skull base repair with the application of cement (Methyl methacrylate) around the cribriform defect. The patient then gradually recovered with no further leak. Discussion: Using bone cement in transcranial CSF leak repair is not commonly reported, compared to the routine use of a pericranial flap. Nevertheless, it showed a high success rate and less recurrence of CSF leak. Lumber drain can be used as a post-op adjuvant technique. Conclusion: We are proposing that the patient’s deterioration was related to the closure of lumbar drain, hence the presence of a one-way valve where air enters and cannot escape with no other means of reducing ICP. We are also demonstrating that bone cement (Methyl methacrylate) can be considered in the management of CSF leak due to skull base defects which is resistant to conventional repair methods including nasoseptal flap and/or pericranial flap.